PENGARUH MINAT KERJA DAN KEMAMPUAN AKADEMIS TERHADAP KESIAPAN MEMASUKI DUNIA KERJA MAHASISWA PENDIDIKAN TEKNIK BANGUNAN - Wikanti Pratiwi; Odih Supratman; Sri Rahayu (Universitas Pendidikan Indonesia (UPI), 2022)
In general, Building Engineering Education students are formed into formal and non-formal teaching staff. But this doesnt rule out the possibility for Building Engineering Education students to get jobs in the industrial field. This goes back to the student in determining his work interests. Work readiness is influenced by many internal and external factors, one of which is work interests and academic abilities that will be a provision when entering the world of work. This study aims to determine the importance of work interest and academic ability to be ready to enter the world of work for Building Engineering Education students Class of 2018. The method used in this study is associative with a quantitative approach. The population in this study was 73 Building Engineering Education Students class of 2018 with a sample of 53 students. The data collection techniques used in the form of documentation and questionnaires or questionnaires with scoring are made using a likert scale. The results of this study are known that, the work interest of Building Engineering Education students class of 2018 shows the level of achievement of respondents in the Category of High Enough for career selection to become teaching staff and the high category for career selection to work in the industrial field. The academic ability of Building Engineering Education students Class of 2018 shows a tendency in the Almost Special category, Work readiness of Building Engineering Education students Class of 2018 shows the level of achievement of respondents in the high category, work interest, and academic ability have a significant influence on the work readiness of Building Engineering Education students class of 2018 with a F value of 26,094